DIAGNOSTIC METHODS OF THERMOELECTRIC PARAMETERS OF SOLIDS (REVIEW) - Фреїк, Дмитро Михайлович; Галущак, Мар’ян Олексійович; Ткачук, Андрій Іванович; Лисюк, Юрій Володимирович; Криницький, Олександр Степанович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The basic measuring methods of thermal conductivity and other thermoelectric parameters (Seebeck coefficient, electrical conductivity) of solids and thin films and plant design for these methods are recited. A number of theoretical and empirical formulae for calculation of these parameters are presented. Measurement accuracy for each of the methods is estimated, and the reasons through which errors arise in the measurement are analyzed.